2013
DOI: 10.1111/ijcp.12238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lipid‐lowering therapy on the prevalence of dyslipidaemia in patients at high‐risk of cardiovascular events in UK primary care – a retrospective database study

Abstract: SummaryAimsTo estimate the prevalence of dyslipidaemias in high-risk patients new to lipid-modifying therapy (LMT), and establish the extent to which these lipid abnormalities are addressed by treatment in UK clinical practice.MethodsThe PRIMULA study was a retrospective analysis, conducted using the UK General Practice Research Database. Two periods were studied as follows: a pretreatment period, defined as the 12 months before initiation of LMT (the index date), and a follow-up period of at least 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Dyslipidemia may be related to other diseases (secondary dyslipidemia) or to the interaction between genetic predisposition and environmental factors [2]. Treatment of dyslipidemia, particularly high levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), is, therefore, a central strategy in the prevention of CVD [7].…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Dyslipidemia may be related to other diseases (secondary dyslipidemia) or to the interaction between genetic predisposition and environmental factors [2]. Treatment of dyslipidemia, particularly high levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), is, therefore, a central strategy in the prevention of CVD [7].…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Studies in other countries have shown that the poor LDL-C control rate for high-risk patients treated in general practice is a global problem [31][32][33]. In South Africa, the control rate for very high-risk patients was reported to be only 26.5%.…”
Section: Treatment Aims and Low-density Lipoprotein Cholesterol (Ldl-mentioning
confidence: 99%
“…It has been estimated that there was 382 million people with type II diabetes mellitus in 2013, while the prevalence of diabetes is estimated to increase by 55% in 2035, reaching a total number of 592 million (1). Dyslipidemia, which is defined by elevated total cholesterol (CHO), triglyceride (TG) and/or low-density lipoprotein cholesterol (LDL-C) levels, and non-optimal levels of high-density lipoprotein cholesterol (HDL-C), is particularly prevalent worldwide (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%